2020
DOI: 10.1523/eneuro.0147-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Stress Induces Prolonged Aggression Increase through Synaptic Potentiation in the Medial Amygdala Circuits

Abstract: Traumatic stress can lead to heightened aggression which may be a symptom of psychiatric diseases such as PTSD and intermittent explosive disorder. The medial amygdala (MeA) is an evolutionarily conserved subnucleus of the amygdala that regulates attack behavior and behavioral responses to stressors. The precise contribution of the MeA in traumatic stress-induced aggression, however, requires further elucidation. In this study, we used foot shock to induce traumatic stress in mice and examine the mechanisms of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(56 citation statements)
references
References 92 publications
(154 reference statements)
2
42
0
Order By: Relevance
“…The three main MeA subregions, MeAa, MeApd, and MeApv, are all involved in aggressive behavior ( Kollack-Walker and Newman, 1995 ; Lin et al, 2011 ; Hong et al, 2014 ; Miller et al, 2019 ; Nordman et al, 2020b ). While we observed that photostimulation of the DR can activate all three subregions, since the MeApd and MeApv have different effects on aggression ( Kollack-Walker and Newman, 1995 ; Lin et al, 2011 ; Hong et al, 2014 ; Miller et al, 2019 ; Nordman et al, 2020a ), it is worth considering that the DR may be shortening an attack through a specific subregion of the MeA. The photostimulation protocol used in this study does not allow for discrimination of these subregions because of their anatomic clustering.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…The three main MeA subregions, MeAa, MeApd, and MeApv, are all involved in aggressive behavior ( Kollack-Walker and Newman, 1995 ; Lin et al, 2011 ; Hong et al, 2014 ; Miller et al, 2019 ; Nordman et al, 2020b ). While we observed that photostimulation of the DR can activate all three subregions, since the MeApd and MeApv have different effects on aggression ( Kollack-Walker and Newman, 1995 ; Lin et al, 2011 ; Hong et al, 2014 ; Miller et al, 2019 ; Nordman et al, 2020a ), it is worth considering that the DR may be shortening an attack through a specific subregion of the MeA. The photostimulation protocol used in this study does not allow for discrimination of these subregions because of their anatomic clustering.…”
Section: Discussionmentioning
confidence: 85%
“…3 F–M , 4 F–U ). The MeA can be divided into three main subdivisions: the anterior MeA (MeAa), the posteriordorsal MeA (MeApd), and the posteriorventral MeA (MeApv), all of which are involved in aggressive behavior ( Kollack-Walker and Newman, 1995 ; Lin et al, 2011 ; Hong et al, 2014 ; Miller et al, 2019 ; Nordman et al, 2020a ). Analysis of c-Fos expression in the MeA revealed that all three regions are activated by photostimulation of the DR ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The CeA also makes reciprocal connections with regions such as the locus coeruleus and BNST, which, as discussed below, are critically engaged in regulating the stress response. Although not a focus of this review [refer to several excellent reviews on the topic (27,28)], it should be noted that the BNST (part of the extended amygdala) plays an increasingly appreciated role in stress responsivity through connections with both the CeA and MeA (29).…”
Section: A Brief Overview Of Amygdala Anatomymentioning
confidence: 99%